An Islamic perspective in the Fiqh (jurisprudence) of banks of milk - Alwan, Ahmed Abbood; El-Seoudi, Abdel Wadoud Moustafa Moursi; Muhammad Husni, Ahmad (American-Eurasian Network for Scientific Information (AENSI Publisher), 2012)
This study tackles a contemporary issue belongs to what iscalled (AL- NawazilFiqh)(Jurisprudence of contemporary issues). The issue discussed in this study is the banks of milk. It is a new issue as it appeared in the seventies of the twentieth century in Europe and U.S.A. Banks of milk have spread in the same way banks of blood, corneas, sperms and prosthetic limbs did. The idea of banks of milk can be simply summarized by collecting milk from volunteer mothers (or paid mothers) who give their milk either because they have more than what their infants need or because the mother has lost a child. The milk is taken from the mother by a sterilized method and kept in sterilized bottles at banks of milk.Opinions and (Fatwas) in this connection have varied widely. Some scholars have disapproved the issue and some have approved due to their different opinions in the issue of breastfeeding. This study will focus on reviewing/and discussing both opinions and views and discuss the reason of dispute among scholars concerning establishing banks of milk. This study also will discuss the scholars’ different opinions about the meaning of breastfeeding, its forbidden quantity and its methodin an attempt to come up with a suitable legitimate judgment that is compatible with our Muslim societies.